Understanding jurisprudence : an introduction to legal theory - Wacks, Raymond (Oxford University Press, 2012)
Perfect for the student new to jurisprudence, this book provides an illuminating introduction to the central questions of legal theory. An experienced teacher of jurisprudence, Professor Wacks' approach is both accessible and entertaining, providing the ideal base for further study